2020
DOI: 10.1016/j.contraception.2019.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine fluid instillation to confirm tubal occlusion after transcervical permanent contraception: A pilot study,

Abstract: Objectives: To determine if women with tubal patency experience more fluid loss compared to those with bilateral tubal occlusion following intrauterine instillation of fluid via a balloon catheter. Study Design:In this prospective cohort pilot study, we enrolled women with prior Essure ® procedures and healthy controls from September 2016-July 2017. We excluded women using an implant or intrauterine device, or with a prior cesarean delivery or permanent contraception procedures other than Essure ® . An infusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…The difference in findings may be due to differences in the HSG imaging and HyCoSy procedures, including variations in the type of contrast agent, pressure injection process, and pressure measurement process ( 32 ). Moreover, Qiang et al ( 9 ) also demonstrated the association between tubal patency and the slope of the pressure curve during HyCoSy, indicating that peak injection pressure could be used as a promising supplement indicator ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference in findings may be due to differences in the HSG imaging and HyCoSy procedures, including variations in the type of contrast agent, pressure injection process, and pressure measurement process ( 32 ). Moreover, Qiang et al ( 9 ) also demonstrated the association between tubal patency and the slope of the pressure curve during HyCoSy, indicating that peak injection pressure could be used as a promising supplement indicator ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown a significant correlation between the volume of contrast agents in HSG and tubal patency in women who have undergone permanent contraceptive procedures. However, the diagnostic efficacy of peak uterine pressure is constrained ( 18 , 19 ). Theoretically, obstruction of the fallopian tubes is expected to increase injection pressure, but there is scant evidence regarding the relationship between peak injection pressure and tubal patency during 4D-HyCoSy.…”
Section: Introductionmentioning
confidence: 99%